Interesting Mechanistic Approach for Nitrogen Heterocycles of Industrial Importance - Zargar, N.D.; Khan, K.Z. (International Journal of Advanced Chemistry, 2018)
Nitrogen heterocycles have played an important role in different industrial sectors.Porphyrins the macrocyclic compounds containing pyrrole rings provide an extremely versatile platform with desired peripheral functionality and metal complexes to form the self assembly under varying reaction conditions. Haemoglobin an iron complex is responsible for binding molecular oxygen and transporting it to different sites. Mechanistically interesting N-heterocycles, Arylidene-1,3-indandione adducts (6) and (7) synthesized frequently are of immense pharmaceutical importance showing fungicidal and bactericidal activities. Nitrogen heteroatom phthalimide derivatives(8),(9) and (10) have been evaluated as possible potential prodrugs. A wide range of Nitrogen heterocycles have been synthesized for every imaginable use in dye and polymer industries.